(untitled) (Asian Journal of Medical Research and Health Sciences, 2026)
Background: Mechanical ventilation is a common intervention used in ICUs. Around 37% of patients getting admitted into Indian ICUs end up needing mechanical ventilation. Early spontaneous breathing trial (SBT) and extubation when tolerated will help avoid complications. Objectives: To study the diagnostic accuracy of RSBI, Rate of change of RSBI & Parasternal Intercostal Muscle Thickness Fraction (PICTF%) as predictors of weaning success. Materials and Methods: This prospective, observational, single-centre cohort study was conducted in the Intensive Care Units (medical, surgical, and emergency ICUs) of MRMC, Kalaburgi. Duration of study was from August 2025 to April 2026. All adult patients admitted to the ICU who required invasive mechanical ventilation for ≥48 hours and subsequently fulfilled criteria to undergo a Spontaneous Breathing Trial (SBT) were screened for enrolment into the study. Clinical, biochemical, and hemodynamic parameters were recorded at admission and after 24 and 48 hours. Results: Both ΔRSBI% and PICTF% emerged as independent predictors of weaning success, whereas RSBI, although still useful, showed comparatively lower discriminative performance. Conclusion: The combination of ΔRSBI% and PICTF% captures both sides of the equation: changing ventilatory pattern and the muscle dynamics that underpin it. This dual perspective is consistent with contemporary pathophysiological models and may explain why the combined index achieved the highest predictive accuracy in our cohort.